French kissed [large type] - Cleeton, Chanel (Cleeton, Chanel. International school series, 2024)
"On the surface, she appears to have it all. If only the facade matched reality... With one year left at the International School in London, Fleur Marceaux is struggling to graduate, her love life is a mess and she can't stop thinking about Max, her ex-boyfriend's best friend. But all that pales in comparison to the blackmailer determined to destoy her. After watching Fleur break his friend's heart, Max Tucker knows to stay away from trouble, despite the crush he's had on her since freshman year. There's a social hieracrchy at the International School, and Max is outside the velvet ropes. But when they're partnered on a project, Max learns there's more to Fleur than meets the eye, and she just might be worth the wild ride. The more time they spend togther, the further Max falls. And when a kiss awakens a passion Fleur never imagined, she's unable to resist Max, who she had thought was all wrong for her but who might be the only thing that's right. But will he stand by her when her secrets are revealed?" --